Inovasi Latihan Footwork Digital Tracking dalam Meningkatkan Kecepatan dan Efisiensi Gerak Pemain Badminton - Muh. Yasa (FKIP UNSULTRA, 2025)
The development of digital technology has significantly influenced training methods in various sports, including badminton. One recent innovation that has attracted attention is the use of digital tracking systems in footwork training to improve athletes' speed and efficiency. This literature review aims to analyze the application of tracking technologies such as motion sensors, sports analytics applications, and IoT-based devices in optimizing badminton players' movement patterns. The literature reviewed was compiled from national and international journals published between 2018 and 2024, covering footwork training, digital technology in sports, and athlete performance. The study results show that digital tracking can provide real-time feedback, quantitative analysis of movement patterns, and enable personalized training programs based on individual weaknesses. This technology has also been shown to improve reaction speed, coordination, and stride efficiency compared to conventional methods. Furthermore, the use of digital tracking helps coaches identify suboptimal movement zones, correct errors, and improve the quality of athlete development monitoring. However, challenges such as device cost, limited access, and the need for coaches to maintain technological literacy remain barriers to implementation. This study concludes that innovative digital tracking-based footwork training has significant potential to become a new standard in developing modern badminton athletes. Further research is recommended to explore the effectiveness of this technology across various age levels and competitive levels.